PENGELOLAAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KOMPETENSI DAN ADAPTABILITAS KARYAWAN PADA ERA SOCIETY 5.0 - Nuranisa Al Azighah; Stephy Fitriady Ali; Muchriady Muchran (CV. Adiba Aisha Amira, 2026)
The era of Society 5.0, characterised by the adoption of smart technology within organisations, demands superior human resource (HR) competencies and adaptability. This study aims to analyse the role of human resource management (HRM) in improving employee competencies and adaptability based on indicators of labour productivity, competency certification, and unemployment rates. The study uses a descriptive quantitative approach with secondary data sources from the Central Statistics Agency (BPS) and the Ministry of Manpower of the Republic of Indonesia (Kemenaker) for the period 2020–2024–2025. Data analysis was conducted through descriptive statistics and trends in changes in these indicators. The results show that labour productivity increased (Rp89.33 million/worker in 2024 compared to Rp87.96 million in 2023) according to Kemenaker data, while the number of certified workers reached ±1.29 million people in 2024, indicating efforts to develop human resource capabilities. In addition, the unemployment indicator shows a downward trend in several periods, reflecting the ability of employees to adapt to new labour market needs. These findings reinforce the strategic role of HRM in developing digital competencies and employee adaptability to support organisational transformation in the Society 5.0 era.